Monetary Policy Response to Oil Price Shocks in Algeria: By Using an Bound Testing Approach (ARDL) - Lakhdimi, Abdelhamid; Boukar, Abdelaziz (Jordan Journal of Economic Sciences, 2021)
This paper aimed to study the mechanisms of the impact of oil price changes on indicators of monetary stability and the mechanism of monetary policy in response to oil shocks, starting the historical development of oil prices from 1970 to 2018. The paper also reviewed the monetary policy measures in Algeria, and used the Autoregression Distributed Lags (ARDL) approach to estimate the econometric model. The study found that the main cause of the oil shocks is due to the geopolitical criseswhere the Bank of Algeria has taken three basic measures in response to the drop in oil prices, namely, the devaluation of the exchange rate, the purchase of sovereign debt, and unconventional financing. As for the econometric study, a cointegrating relationship was found between the variables of the study. The analysis of the impulse function response test showed that two variables were more affected by the oil price shocks: inflation and the monetary mass.